Penerapan Model Pembelajaran Latihan Inkuiri untuk Meningkatkan Keaktifan Lisan dan Hasil Belajar dalam Pembelajaran Fisika Pada Siswa Kelas VII SMPN 2 Pandak Bantul - Widodo W; Dwi Nursati (Department of Physics, Sebelas Maret University, 2016)
Based on the observations in SMP Negeri 2 Pandak, it was found that the activity and spirit of students in learning activities were low. The student oral was low and the quality of student learning was under the minimal completeness criteria. The aims of this research were to improve students learning outcomes of cognitive aspects, affective aspects of students andpsychomotor aspects of students after attending a t inquiry practice learning model. Design research is a classroom action research (CAR), which consists of 3 cycles. Subjects in this study are students of class VII-D SMP Negeri 2 Pandak, Bantul. The research instrument that was used consisted of the lesson plan, student worksheets, observation sheet to observe the implementation of inquiry practice learning model, students orally activities, affective aspectsof students, and psychomotor aspects of the student, while the tests was used to measured cognitive aspects of students. The results showed that there were an increase in oral activity ofstudents, learning outcomes of cognitive aspects, affective aspects, and psychomotor aspects of students.